2023
DOI: 10.3390/s23239498
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of AI-Based Wearable Sensors for Digital Health Technology: A Review

Shaghayegh Shajari,
Kirankumar Kuruvinashetti,
Amin Komeili
et al.

Abstract: Disease diagnosis and monitoring using conventional healthcare services is typically expensive and has limited accuracy. Wearable health technology based on flexible electronics has gained tremendous attention in recent years for monitoring patient health owing to attractive features, such as lower medical costs, quick access to patient health data, ability to operate and transmit data in harsh environments, storage at room temperature, non-invasive implementation, mass scaling, etc. This technology provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 251 publications
0
11
0
Order By: Relevance
“…The results support the feasibility of the proposed system as a clinical decision tool for Parkinsonian tremor-severity automatic scoring [ 57 ]. Another study demonstrated that the inaccuracies in heart rate data can be rectified with the sensors, thus ensuring the reliability and precision of the medical devices [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results support the feasibility of the proposed system as a clinical decision tool for Parkinsonian tremor-severity automatic scoring [ 57 ]. Another study demonstrated that the inaccuracies in heart rate data can be rectified with the sensors, thus ensuring the reliability and precision of the medical devices [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rather than relying on static rules, these systems depend on machine learning algorithms to analyze real-time data. 267 This empowers them to make decisions based on the current context, learning and adapting over time. 268…”
Section: Smart Wearable Microfluidic Devicesmentioning
confidence: 99%
“…The evaluation of data is aided by the integration of AI and machine learning algorithms in RHMS. These algorithms provide insights, find patterns in large datasets, and analyse them [106]. However, the calibre of training data and continuous validation procedures determine how accurate are AI-driven evaluations.…”
Section: Data Accuracy and Evaluationmentioning
confidence: 99%